An exploratory survey of online shoppers in Malaysian / Dr Kiranjit Kaur … [et al.] - Kaur, Kiranjit (Associate Professor Dr); Iyer, Mangalam Gopala (Associate Professor); Abdul Jabar, Noraziah; Abdul Hamid, Norliza (2005)
This study examines the patterns of e-commerce transactions in Malaysia by determining the criteria that influenced shopping decisions made by 126 online shoppers. The study also identified problems faced by consumers and what they felt about the way retailers addressed their grievances. Saving time and convenience were cited by the shoppers as the main reasons for shopping online. Key problems faced by consumers were returning unwanted or damaged products and cancellation of orders. Consumers also feared a lack of privacy and security that may result in their names and addresses being put on unwanted mailing lists, receiving spam mail, and the possible abuse of credit card information given online. There were complaints also about a few traders who were slow to respond to consumer complaints about their grievances, and affected consumers resolved to avoid those sites in future. Most of the shoppers thought it is crucial for the country to examine and improve upon the existing regulatory procedures in order to raise consumer confidence in e-commerce.